INCREASING CADRE COMPETENCE AS MENTORS FOR PREGNANT WOMEN - Wahyuni, Sri; Rahayu, Tutik; Aspihan, Moch; Neng Ayu Sri wahyuni (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Background Pregnancy is a woman's maturation process that requires adaptation to become a mother. This role change is not an easy thing and a companion or mentor is needed. Mentoring for pregnant women is done by optimizing human resources in the community. Method: The activity was carried out in Bandarharjo Village, North Semarang sub-district, Semarang City with 36 potential mentors. The activities were divided into 5 (five) stages, namely (1) Socialization, (2) competency improvement, (3) Practicum (4) Monitoring and evaluation. Results: The pre-test describes that most of the mentors have a low level of knowledge, namely 24 people (66.7%), have a bad attitude as many as 20 people (55.6%), and do not have good mentoring skills. Post-test data obtained, that most of the mentors have moderate knowledge, namely as many as 22 people (61.11%), 34 people (94.4%) have a good attitude and as many as 34 people (94.4%) have moderate skills. Conclusion: There is an increase in the knowledge, attitudes, and skills of mentors after being given training.